Alkaline sulfonation and thermomechanical pulping pretreatment of softwood chips and pellets to enhance enzymatic hydrolysis. (November 2020) - Wu, Jie; Chandra, Richard; Takada, Masatsugu; Del Rio, Pablo; Kim, Kwang Ho; Kim, Chang Soo; Liu, Li-yang; Renneckar, Scott; Saddler, Jack
Graphical abstract: Highlights: Alkaline sulfonation and thermomechanical pulping effectively pretreats softwoods. Sulfonation predominantly occurs within the secondary cell wall lignin. Softwood pellets are more recalcitrant than softwood chips. Abstract: To assess the impact of alkalinity on sulfonation and the enzyme-mediated hydrolysis of softwood cellulose, Lodgepole pine chips were impregnated with 8% sodium sulfite and increasing loadings of sodium carbonate before thermomechanical pulping. It was apparent that alkali addition enhanced lignin sulfonation with an additional 4% loading of sodium carbonate proving optimal. TEM indicated that sulfonation predominantly occurred within the secondary-cell-wall lignin, increasing cellulose accessibility to the cellulase enzymes. Although increasing alkalinity did not significantly enhance lignin sulfonation, likely due to the lower acetyl content of the softwood chips, it increases mannan solubilization. Despite their smaller particle size, softwood pellets were more poorly sulfonated, probably due to their higher lignin content and lower amount of acid groups. This more condensed lignin structure was confirmed by 2D-NMR and GPC analyses which indicated that the EMAL derived from softwood pellets contained less native β-O-4 linkages and had a higher molecular weight.